21-03 A Measurement and Evaluation Roadmap to Support Social Impact Investment in Canada - Hurley, Jeremiah; Milinkovic, Deborah; Feeny, David; Guindon, Emmanuel; Sweetman, Arthur; Tarride, Jean-Éric Tarride (CHEPA WORKING PAPER, 2021)
Social finance offers innovative ways to finance solutions to many of society’s most challenging problems by attracting private investments that create both financial returns for investors and desired social and environmental impacts. Community Foundations of Canada (CFC) is working with sector partners to develop a social-finance platform called Outcomes Canada (OC) to facilitate community-driven social finance. Many community initiatives face significant capacity challenges and resourcing gaps. At present, community initiatives bear the burden of navigating a highly decentralized financing ecosystem to secure funding and other support needed to build their capacity and achieve desired outcomes. At the same time, governments, social financiers, philanthropists, and academics seek to find and support community initiatives that are producing results. This gap reflects the need for new tools, innovative financing vehicles and streamlined approaches to support community-driven outcomes in Canada.
Keywords: Canada; Libre accès; Université

21-03 A Measurement and Evaluation Roadmap to Support Social Impact Investment in Canada - Hurley, Jeremiah; Milinkovic, Deborah; Feeny, David; Guindon, Emmanuel; Sweetman, Arthur; Tarride, Jean-Éric Tarride (CHEPA WORKING PAPER, 2021)
Social finance offers innovative ways to finance solutions to many of society’s most challenging problems by attracting private investments that create both financial returns for investors and desired social and environmental impacts. Community Foundations of Canada (CFC) is working with sector partners to develop a social-finance platform called Outcomes Canada (OC) to facilitate community-driven social finance. Many community initiatives face significant capacity challenges and resourcing gaps. At present, community initiatives bear the burden of navigating a highly decentralized financing ecosystem to secure funding and other support needed to build their capacity and achieve desired outcomes. At the same time, governments, social financiers, philanthropists, and academics seek to find and support community initiatives that are producing results. This gap reflects the need for new tools, innovative financing vehicles and streamlined approaches to support community-driven outcomes in Canada.
Keywords: Canada; Libre accès; Université